Oxygenation and adenosine deaminase support growth and proliferation of ex vivo cultured Drosophila wing imaginal discs - Straßburger, Katrin; Boutros, Michael; Teleman, Aurelio A. (Development, 2017)
The Drosophila wing imaginal disc has been an important model system over past decades for discovering novel biology related to development, signaling and epithelial morphogenesis. Novel experimental approaches have been enabled using a culture setup that allows ex vivo cultures of wing discs. Current setups, however, are not able to sustain both growth and cell-cycle progression of wing discs ex vivo. We discover here a setup that requires both oxygenation of the tissue and adenosine deaminase activity in the medium, and supports both growth and proliferation of wing discs for 9 h. Nonetheless, further work will be required to extend the duration of the culturing and to enable live imaging of the cultured discs in the future.
Gesehen am 17.10.2018